LOVE OF MONEY, ETHICAL REASONING, MACHIAVELLIAN, QUESTIONABLE ACTIONS : THE IMPACT ON ACCOUNTING STUDENTS’ ETHICAL DECISION MAKING BY GENDER MODERATION - Ratih Yeltsinta; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
This study aims to analyze whether there is a relationship between the level of love of money, ethical reasoning, Machiavellian on questionable actions in accounting students to ethical decision making in accounting violations by gender moderation. The samples were taken by using the method of data collection is called purposive sampling. The samples used as many as 30 respondents. The data obtained were analyzed using analysis techniques PLS (Partial Least Square) via software SmartPLS. The results of this study indicated that there is a relationship between the level of love of money on accounting students to ethical reasoning and Machiavellian level as well as the relationship between ethical reasoning and Machiavellian against questionable action. The results also showed that the action of questionable actions also affect how accounting students make ethical decisions accounting violations. However, gender differences between male and female accounting students do not moderate the relationship between the love of money, ethical reasoning, Machiavellian, and questionable actions.